Detrusor Underactivity: The Current Concept of the Pathophysiology. Issue 3 (14th August 2014) - YOSHIDA, Masaki; YAMAGUCHI, Osamu
<x xml:space="preserve">Abstract</x> Based on evidence from available literature, we review the pathophysiology of detrusor underactivity (DU). DU is likely to be multifactorial. Aging reduces detrusor activity, but other concomitant causes may aggravate this condition, resulting in decrease of detrusor contractility. Impaired detrusor contractility has been regarded as a major etiologic factor of DU. However, a more complex pathology has been proposed. As contributing factors to DU, we discuss disturbances of the sensory afferent side of the micturition reflex, the central nervous system (CNS) and the efferent side of the reflex, including nerves and the detrusor muscle. Particularly, dysfunction of afferent nerves in the bladder and urethra may play a crucial role in the pathogenesis of DU. In addition, recent studies suggest that chronic bladder ischemia and resultant oxidative stress cause detrusor overactivity progressing to DU and inability to empty the bladder.